(untitled) (Journal of Fiber Bioengineering and Informatics, 2022)
The main aim of this work is to develop TiO2 nanoflowers coated polyester (PET) fabric for antibacterial and UV protection applications. The TiO2 nanoflowers were grown on PET fabric by a two-step method. In first step, the polyester fabric was seeded using sol-gel method and in second step the nanoflowers were grown on the seeded PET fabric by hydrothermal method. The surface morphology and elemental analysis were carried out by using Scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS) and atomic force microscopy (AFM). The effect of TiO2 nanoflowers on the functional properties were examined based on antibacterial activity, UV blocking and physiological comfort properties. The TiO2 nanoflowers coated fabric demonstrated the ability to kill the bacteria and to prevent its growth. During quantitative assessment the 96% and 99% of bacterial reduction was found for E. coli and S. aureus, respectively. The TiO2 nanoflowers coated polyester fabric exhibited excellent UV blocking properties. The analysis of thermal properties, water vapor permeability and air permeability was also performed to study the physiological comfort of the TiO2 nanoflowers coated fabrics. The thermal conductivity and thermal absorptivity was found to increase for TiO2 nanoflowers coated fabrics. Moreover, no significant decrease in water vapor permeability and air permeability was noticed by the growth of the TiO2 nanoflowers. The developed PET fabrics could be used for functional applications.